Pengaruh motivasi kerja, lingkungan kerja, dan budaya organisasi terhadap kepuasan kerja para guru di Yayasan Nasa Professional School Depok - Santika, Vireja; Wolor, Christian Wiradendi; Handaru, Agung Wahyu (ARKA INSTITUTE, 2023)
This study attempts to ascertain the potential impact of work motivation, work environment, and organizational culture on job satisfaction of teachers at Yayasan Nasa Professional School. This study uses a survey methodology with a quantitative orientation. The survey involved a population of 103 teachers from SMP, SMA, and SMK Putra Bangsa which are educational institutions affiliated with Yayasan Nasa Professional School. The sampling methodology uses saturated or census sampling, which means including every individual in the population in the sample. The methodology used for data analysis is multiple linear regression analysis. A significant and positive partial correlation was found between work motivation and job satisfaction, work environment and job satisfaction, and organizational culture and job satisfaction. The results of the study indicate that work motivation, work environment, and organizational culture all have a large and positive influence on job satisfaction. It can be concluded that with increasing work motivation, work environment and organization, job satisfaction will also increase.